The psychological (ab)use of timeouts in professional tennis - Blything, L. P.; Blything, R. (International Journal of Performance Analysis in Sport, 2026)
The (ab)use of timeouts as a tool for swinging momentum is a long-standing psychological question in tennis. We provided the first real-world quantitative investigation of this, through an archival analysis of bathroom timeouts taken between sets in professional tennis matches [timeout N = 366 following stringent data preprocessing of confounds]. Our study revealed three key findings. First, the majority of bathroom timeouts were taken by players who lost the prior-set, suggesting that the decision to take a timeout is triggered by negative momentum. Second, the likelihood of recovering from a lost set to win the next set was greater after a bathroom timeout, relative to stringently controlled baseline data where no timeouts were taken. Third, follow-up analyses on the extent to which unforced-errors contributed to the forms of points won and lost, indicated that the timeout advantage is a combination of both the strategist benefitting from the opportunity to personally reset, and a disruption of the rhythm of the opponent, rather than being disproportionally driven by one player. Together, these pioneering findings uniquely inform players and tennis governing bodies about the influence of timeouts and, more broadly, elucidate the role that stoppages can play in sport for altering momentum.